Investigation of the direct compression properties of microcrystalline starch (MCS) as a filler/binder/disintegrant in metronidazole tablet formulation. (2010) - Apeji, Y. E.; Oyi, Avosuahi; Musa, H.; Olowosulu, A. K.
No abstract available